Employment and income of the populations of the republics of Tuva and Bashkortostan (2010–2020) - Baimurzina, Guzel R.; Kabashova, Elena V. (The New Research of Tuva, 2022)
The article examines employment and income issues of the populations in the Republic of Tuva and the Republic of Bashkortostan, including those relating to the position of the main ethnic groups. The analysis is performed in the context of the concept of human development and the possibility approach. Authors provide insight into the general and special features of employment, income and social well-being of the populations in the republics of Tuva and Bashkortostan for 2010–2020, including those in the context of ethnic groups. Combinations of objective data and subjective estimates of the population that characterize the spheres of employment and income are consistently analyzed. The empirical base of the research is consisted of official statistics (Rosstat) and the results of special sociological studies conducted in Tuva and Bashkortostan in 2021.The ethnic factor in the republics consists in the level and types of economic activity of the population. The titular ethnic groups are more represented in the budget-funded sectors of the economy, the spheres of art and culture constitute a special “ethnic niche”. Ethnic differences in the republics are an objective consequence of sociocultural and resettlement factors rather than of discriminatory ones. The ethnic features of employment reveal themselves better in Tuva than in Bashkortostan, probably due to the greater representation of the titular ethnic group and a smaller quantity of intercultural interactions in the structure of the region’s population.In both republics, there is an increasing instability of the labor market, a relatively high level of informal employment, a reduction in real incomes of the people and incomes from entrepreneurial activity. The life quality of the population in Tuva is significantly lower than that of the people in Bashkortostan and Russia as a whole due to the underdeveloped structure of the economy and low economic activity of the population. Bashkortostan is also characterized by processes that hinder human development.
Keywords: standard of living; life quality; income; employment; social well-being; human potential; Republic of Tuva; Republic of Bashkortostan; Tuvans; Bashkirs